Interplay of p23 with FKBP51 and their chaperone complex in regulating tau aggregation - Pijush Chakraborty; Markus Zweckstetter (Nature Communications)
Abstract The pathological deposition of tau and amyloid-beta into insoluble amyloid fibrils are pathological hallmarks of Alzheimer’s disease. Molecular chaperones are important cellular factors contributing to the regulation of tau misfolding and aggregation. Here we reveal an Hsp90-independent mechanism by which the co-chaperone p23 as well as a molecular complex formed by two co-chaperones, p23 and FKBP51, modulates tau aggregation. Integrating NMR spectroscopy, SAXS, molecular docking, and site-directed mutagenesis we reveal the structural basis of the p23-FKBP51 complex. We show that p23 specifically recognizes the TPR domain of FKBP51 and interacts with tau through its C-terminal disordered tail. We further show that the p23-FKBP51 complex binds tau to form a dynamic p23-FKBP51-tau trimeric complex that delays tau aggregation and thus may counteract Hsp90-FKBP51 mediated toxicity. Taken together, our findings reveal a co-chaperone mediated Hsp90-independent chaperoning of tau protein.